Pengaruh Basis Carbopol Terhadap Formulasi Sediaan Gel Dari Ekstrak Daun Katuk (Sauropus androgynus (L.) Merr) - Sheila Meitania Utami (Edu Masda Journal, 2019)
Carbopol research has been studied on gel formulation from katuk leaf extract (Sauropus androgynus (L.) Merr). This study aims to make formulations and determine the concentration of carbopol as a base that can produce a good gel preparation. This research used 3 gel formulations, with variation of carbopol 2%, 3,5% and 4% concentration. The result of organoleptic observations in formulations I, II, and III have not changed in odor and color, but there are differences in the form in which formulation I form is thick, formulation II is viscous, and formulation III viscous form is rather stiff. The result of homogenity observation on formulation I, II and III did not show any coarse particles on the glass object. The results of pH measurements in formulations I, II, and III did not change significantly pH that is in the formulation I 5,61; formulation II 5,42 and formulation III 5,61. The result of the measurement of the scattering power in the formulations I, II, and III did not reach the scattering power requirement because it has an average power range of 2,05 cm to 4,05 cm. The conclusions of formulation I by gel preparation from katuk leaf extract with 2% of carbopol base concentration had the best evaluation.